2018
DOI: 10.1177/1937586718779219
|View full text |Cite
|
Sign up to set email alerts
|

The Role of Hospital Design in Reducing Anxiety for Pediatric Patients

Abstract: The study supports the use of Ulrich's theory of supportive design to children's healthcare environments, though what is experienced as supportive design will vary by the developmental stage of the child.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
13
0
1

Year Published

2019
2019
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(14 citation statements)
references
References 20 publications
0
13
0
1
Order By: Relevance
“…Although visiting the imaging department is stressful in most children and adolescents, the architecture of the department has been recognized as a contributor to stress relief or exacerbation. Poor design of therapeutic environments can adversely affect the health and wellbeing of the child, which is why more attention is now being paid to planning optimal environments for unwell pediatrics [16,17]. In the present study, space staining was identified as the third most applicable method for attracting child cooperation and reducing stress in children under and over 8 years of age.…”
Section: Discussionmentioning
confidence: 76%
“…Although visiting the imaging department is stressful in most children and adolescents, the architecture of the department has been recognized as a contributor to stress relief or exacerbation. Poor design of therapeutic environments can adversely affect the health and wellbeing of the child, which is why more attention is now being paid to planning optimal environments for unwell pediatrics [16,17]. In the present study, space staining was identified as the third most applicable method for attracting child cooperation and reducing stress in children under and over 8 years of age.…”
Section: Discussionmentioning
confidence: 76%
“…Due to the limitations imposed by the children's age on their cognitive abilities, the main questionnaires and interviews focused on the accompanying people/parents. Similar studies have focused on parents as the object of information collection (e.g., Cartland et al, 2018). In this study, children aged 3 and under accounted for 49.7% of the sample, children aged 4-6 accounted for 34.4% and preschool children were the main waiting population.…”
Section: Analysis (1) Sample Validation and Reliability Analysismentioning
confidence: 67%
“…Design goals include exposure to nature and art and appropriate ceiling design, acoustics and color. Supportive design theory is applicable to childcare settings [2]. Providing positive resources and conditions, such as control, distraction and social interaction, can reduce or even prevent children's environmental stress [3].…”
Section: Background and Research Goals 1evidence-based Designmentioning
confidence: 99%
See 2 more Smart Citations